Spectra of Cherenkov and transition radiation excited by a train of electron bunches in dielectric structures of rectangular cross-section - Onishchenko, I.N.; Onishchenko, N.I.; Sotnikov, G.V. (Вопросы атомной науки и техники, 2006)
The peculiarities of radiation spectra of a single relativistic electron bunch or train of bunches in an infinite rectangular dielectric waveguide, in a semi-infinite dielectric waveguide, and in a dielectric waveguide of finite length were theoretically explored. Single-mode and multimode modes were surveyed. In the first case, the excited fields corresponding to Cherenkov and transition radiation were identified. In the second case, the substantial growth of field amplitude was obtained due to interference of many excited transversal modes. Limitation on maximum field amplitude and amount of contributing bunches caused by the fields removal with a group velocity was found. The features of excited spectra caused by a regular sequence of bunches were investigated. Selective excitation of transversal modes and corresponding field waveform were considered for the arbitrary rectangular geometry. Исследовано возбуждение кильватерного поля электронными сгустками и их последовательностью в прямоугольных диэлектрических структурах: бесконечном волноводе, полубесконечном волноводе и волноводе конечной длины. Досліджене збудження кільватерного поля електронними згустками та їх послідовністю в прямокутних діелектричних структурах: необмеженому хвилеводі, напівобмеженому хвилеводі та хвилеводі кінцевої довжини.